Pencabutan Kabel Pacu Alat Elektronik Kardiak Implan - I Made Putra Swi Antara; Yoga Yuniadi (The Indonesian Heart Association, 2013)
As more people are living longer with more significant cardiac disease,permanent pacemakers (PPMs) and implantable cardioverter-defibrillators(ICDs) are being inserted more frequently each year. Beginning early in the21st century, there has also been an expansion in the indications for cardiacimplantable electronic devices (CIED, a term which includes PPMs andICDs), and device therapy has become more complex, frequently involvingmultiple leads per patient. In turn, there will be more occasion where thelead removal for these CIED will be necessary.A 6 y.o. patient was incidentally found to have a fractured pacemaker leadduring during routine x-ray for his respiratory tract infection. The pacemakerwas inserted 5 years ago, indicated for the permanent total atrioventricularblock developed after total correction surgery in Tetralogy of Fallot. Thelead fracture was thought to be caused by a phenomenon known as thesubclavian crush syndrome. A transvenous lead extraction in this patientwas only partially successful, leading to a surgical removal of the remaininglead. A new permanent pacemaker along with a new lead in the apexwas successfully inserted before the surgery.There are different levels of recommendations on whether a lead shouldbe extracted or left behind. And in times where removal was needed,new specialized tool and techniques have developed in the last decade forthe safe and successful retrieval of implanted pacemaker leads.